2022
DOI: 10.1101/2022.03.01.22271659
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural deviations of the posterior fossa and the cerebellum and their cognitive links in a neurodevelopmental deletion syndrome

Abstract: High-impact genetic variants associated with neurodevelopmental disorders provide biologically defined entry points for etiological discovery. The 3q29 deletion (3q29Del) is one such variant that confers a ~40-fold increased risk for schizophrenia, and a ~30-fold increased risk for autism. However, the specific neural mechanisms underlying this link remain largely unknown. Here, we report the first in vivo quantitative neuroimaging study in 3q29Del subjects (N = 24) and healthy controls (N = 1,608) using struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 182 publications
(224 reference statements)
1
13
0
Order By: Relevance
“…Our group has also shown quantitively that study subjects with 3q29DS exhibit abnormal cerebellar volumes compared with HCs (32). In the current study, we demonstrate that these neuroanatomical phenotypes may have clinical relevance.…”
Section: Introductionsupporting
confidence: 71%
See 3 more Smart Citations
“…Our group has also shown quantitively that study subjects with 3q29DS exhibit abnormal cerebellar volumes compared with HCs (32). In the current study, we demonstrate that these neuroanatomical phenotypes may have clinical relevance.…”
Section: Introductionsupporting
confidence: 71%
“…Recent radiological findings by our team have revealed that cerebellar hypoplasia and cystic/cyst-like malformations of the posterior fossa, are significantly elevated in 3q29DS (10). Our group has also shown quantitively that study subjects with 3q29DS exhibit abnormal cerebellar volumes compared with HCs (32). In the current study, we demonstrate that these neuroanatomical phenotypes may have clinical relevance.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…These studies indicate that the genomic insults in Williams syndrome and 22q11.2 deletion syndrome impact visual-motor integration ability above and beyond the insult to cognitive ability; the present study suggests the same may be true in the context of the 3q29 deletion. Indeed, previous work by our team has identified a significant association between VMI performance and cerebellar white matter volume (Sefik et al, 2022), suggesting that VMI performance in 3q29del is related to a brain region distinct from those canonically involved in cognition, but likely to contribute to visuo-spatial function.…”
Section: Discussionmentioning
confidence: 87%